Effects of injection pressure on wellbore stress using flow-stress coupling method - Bataee, M. (Society of Petroleum Engineers, 2016)
Enhanced Oil Recovery (EOR) injection methods are increasingly applied globally as the effective method in oil wells. Fluid injection alters the formation stress around the wellbore. In this study an iterative coupling method is proposed to evaluate wellbore stresses for one cycle of water alternating gas (WAG) injection. The effective parameters such as pressures, temperature, saturations and stresses are obtained for the multiphase flow condition using mathematical modeling. In this study, finite difference method is used to calculate pressure, temperature and saturations; and finite volume method is applied to evaluate stresses. Iterative coupling method is used to improve the accuracy of the results. The results show the pressure is boosted around wellbore after injection and how the water bank is pushed by injected gas. Maximum value of radial stress is obtained in the direction of horizontal maximum in-situ stress. Maximum value of tangential stress is determined in the direction of horizontal minimum in-situ stress. Vertical stress around the wellbore is not related to horizontal maximum and minimum in-situ stresses. The shear stress values are small in comparison with other stress types. The accuracy of model results are increased by iterative coupling, which the maximum correction is about 20 psi (0.14 MPa) for pressure. The developed model is capable to be applied in the wellbore to ensure stability for different injection or production cases. Copyright 2016, IADC/SPE Asia Pacific Drilling Technology Conference.